Recruitment in Swarm-Founding Wasps: Polybia occidentalis Does not Actively Scent-Mark Carbohydrate Food Sources - Benjamin J. Taylor; Erik V. Nordheim; Teresa I. Schueller; Robert L. Jeanne (Psyche: A Journal of Entomology)
Scent marking food resources is expected to enhance foraging efficiency reducing search time. Many social bees exhibit this behavior, but scent-marking is absent in social wasps, except for Vespa mandarinia. We tested for scent marking in the swarm-founding wasp, Polybia occidentalis. This wasp has moderately large colonies and utilizes resources that are concentrated in time and space, making scent marking profitable. Also, this wasp uses chemical markings to lead nestmates to a new nest site during swarm emigration, making it possible that it could use the same behavior to recruit nestmates to a food source. Foragers from 11 colonies were given a choice between a previously visited feeder and an unvisited one, both containing a rich, unscented sucrose solution. There was no difference in the number of visits to the two treatments. However, some individuals chose the feeder on one side more often. We conclude that foragers of this species of wasp do not use odor marks left behind by nestmates to find food, but they do exhibit the tendency, when returning to a food source that has not been depleted, to choose a resource based on its relative position, presumably by using visual cues.